A new approach towards waste container detection in smart cities - Valente, Miguel (2021)
This paper presents a new approach to help redesigning waste management for the cities of the future. The current state of tracking waste containers is rigid, inefficient and hard to oversee. Although attempts have been made in the past using radio-frequency identification for waste container detection, it has shown problems like flexibility, cost and environmental impact. We propose and demonstrate a solution based on the use of computer vision techniques, for object detection and classification, towards the differentiation between different types of waste containers.